Theoretical of the precondition of construction of the concept of continuous ecological education - R V Oparin (RUDN Journal of Psychology and Pedagogics, 2010)
In given article the essence, structure, principles, the maintenance of the concept of continuous ecological education in Republic Altai are considered. The basic directions of realization of the concept and expected results are shown.